The necessity of effective teaching of English at all levels of education in Nigeria - Sunday Abraham Unubi (UAD TEFL International Conference)
Since language is dynamic, and teaching is a dynamic tool of instructing and training someone (the learner) for desired change in their lives, behaviors, experiences, and statuses, it also requires a dynamic and an experienced mind to carry it out. In its methodology, the study adopted both the primary and secondary sources of data gathering technique. Observational examination of both teachers and learners of the English language constituted the primary source while extant material dealing with the teaching and learning of English comprised the secondary data. The observation mainly bordered on phonetics and phonology, that is, how some Nigerian teachers of English realize or articulate some sounds and words of English, which in turn has impacted negatively on the learner. These sounds and words are divided into two groups – A and B, and group A is further divided into vowel and consonant sounds. We also presented the charts of the vowels and consonants of English to guide us in our analysis. The result of this investigation showed that mother tongue interference is the main factor responsible, and that teachers need to do extra work on themselves for satisfactory and positive learning outcomes on the learners, which is a direct consequence of effective teaching.